Intra-group heterogeneity in collective contests - Shmuel Nitzan; Kaoru Ueda (Center for Economic Studies and ifo Institute (CESifo), 2013)
Collective contests are examined permitting heterogeneity of stakes within every competing group. Our first concern is whether unequal distribution of stakes in a group can enhance its win probability. Our second concern is whether a large stake in a group can be individually disadvantageous. We find that if a contest is sufficiently hard for a group, the answers to these questions are positive under plausible conditions. In such situations, monopoly of the private stake is most effective in enhancing the group's performance. Ironically, in the same cases, the welfare of many group members would be negatively related to the size of their individual stake.
Keywords: D70; D71; D72; 330; collective contest; intra-group heterogeneity; elasticity of marginal effort costs; unequal stakes and group performance; military alliance; exploitation of the large; Arbeitsgruppe; Wettbewerb; Arbeitsleistung; Verteilungskonflikt; Public Choice; Bündnissystem; Theorie